2013
DOI: 10.4038/jnsfsr.v41i1.5326
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of water table and groundwater quality of the karst aquifer of the Jaffna Peninsula-Sri Lanka

Abstract: Abstract:The Miocene limestone bedrock of the Jaffna Peninsula of Sri Lanka extends below the sea level and is an into the soil and forms a layer of freshwater in the limestone above the seawater. This freshwater is in the form of a convex lens, which thins out towards the coast and the lower part of the lens is a transitional zone where the freshwater becomes increasingly brackish with depth. The thickness of the lens freshwater in the lens is able to sustain irrigation and domestic usage till the end of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 3 publications
0
4
1
Order By: Relevance
“…According to the FAO classifications, a major portion of the study area consists of unsuitable groundwater for agriculture. Even though most of the previous studies have reported that the groundwater is suitable for irrigation in the Jaffna Peninsula [22,33,34], the results of the present study showed that there is a risk when utilizing this water for irrigation. Over-extraction of groundwater to facilitate the passionate expansion of agriculture, development projects and resettlements that took place during the post-war period can be identified as the main reason for the deterioration in water quality.…”
Section: Groundwater Quality and Availability Of The Jaffna Peninsulacontrasting
confidence: 79%
“…According to the FAO classifications, a major portion of the study area consists of unsuitable groundwater for agriculture. Even though most of the previous studies have reported that the groundwater is suitable for irrigation in the Jaffna Peninsula [22,33,34], the results of the present study showed that there is a risk when utilizing this water for irrigation. Over-extraction of groundwater to facilitate the passionate expansion of agriculture, development projects and resettlements that took place during the post-war period can be identified as the main reason for the deterioration in water quality.…”
Section: Groundwater Quality and Availability Of The Jaffna Peninsulacontrasting
confidence: 79%
“…The most probable cause for the high concentrations of nitrate in wells could be the excess fertilizers leached to the shallow groundwater. The calcic soil favours the leaching of nitrate N as it has high permeability [ 21 ]. The addition of abundant nitrogenous waste and synthetic and animal fertilizers is identified as the major cause for nitrate contamination.…”
Section: Resultsmentioning
confidence: 99%
“…However, documentation on the long-term effects of salinity on coastal paddy fields remains limited. Most of the coastal studies that have researched and examined water quality parameters, including salinity levels in groundwater systems in the area, have focused on a specific period [30] or short term [27,[31][32][33], the longest period being a one year trend [23,26,34]. This present study is aimed at investigating the spatial and temporal changes in groundwater salinity of Jaffna Peninsula over the last two decades.…”
Section: Introductionmentioning
confidence: 99%